ISTIKHDĀM THARĪQAH AL GHINĀ’ LI AL HIFDZI AL MUFRADĀT AL LUGHAH AL ‘ARABIYAH - Zahro, Aminatuz; Yunus, Moch; Shobirin, Shobirin (STIQ Amuntai, 2024)
Education in Indonesia is currently competing to require the nation's children to be able to master various foreign languages, one of which is Arabic. Good mastery of Arabic needs to be based on the number of mufrodat that are mastered. This research uses qualitative research methods conducted on class VII students of SMP Qur'ani Dliyaul Qur'an Menemen as the research population. The research subjects, consisting of people, are the researchers themselves and data collectors. Data collection methods include interviews, questionnaires, field data, photos, documents, memos, and other notes. This research data was taken from 15 students. As a result of the discussion on the use of the singing method in memorizing the mufradat, the students became more enthusiastic and more active in learning Arabic and were even more unified in singing the Arabic mufradat. Without memorizing it manually, the students already memorized the mufradat with this singing method. According to Bonnie and John, there are benefits to the method. Singing helps achieve abilities in developing thinking power, helps channel emotions such as happiness or sadness through the content of song or singing lyrics, and helps add new vocabulary through song lyrics or chanting. The aim of this research is that more students will be interested in memorizing Arabic muhradat for students who are anxious and lazy. Based on the assessment of experts, the use of the singing method in memorizing mufradat is very interesting for students who are less enthusiastic about learning; therefore, the researchers used this method for SMP Qur'ani Dliyaul Qur'an.